Acute stress of the typical disinfectant glutaraldehyde-didecyldimethylammonium bromide (GD) on sludge microecology in livestock wastewater treatment plants: Effect and its mechanisms. (1st December 2022) - Li, Yuxin; Ling, Jiayin; Xue, Jinghao; Huang, Junwei; Zhou, Xiao; Wang, Fei; Hou, Waner; Zhao, Jianbin; Xu, Yanbin
Highlights: GD stress affected nitrogen metabolism in the WWTP more obviously than COD removal. Denitrifying bacteria are more tolerant to GD than AOB and NOB. Transcripts of aminoglycoside resistance genes are more abundant when GD <1 mg/L. Denitrifiers are the dominant genus owing to their easy access of resistance genes. GD might induce the horizontal transfer of antibiotic resistance genes. Abstract: Glutaraldehyde and didecyldimethylammonium bromide (GD) is a disinfectant widely used to prevent African swine fever (ASF) in livestock farms. However, the effect of residual GD on the activated sludge microbial ecology of receiving wastewater treatment plants (WWTPs) remains largely unknown. In this study, seven simulated systems were established to research the effects of GD on WWTPs and reveal the underlying mechanisms of microecological responses to GD at different concentrations. Both the nitrogen and carbon removal rates decreased with increasing GD concentrations, and nitrogen metabolism was inhibited more obviously, but the inhibition weakened with increasing stress duration. Microorganisms activated their SoxRS systems to promote ATP synthesis and electron transfer to support the hydrolysis and efflux of GD by producing a small number of ROS when exposed to GD at less than 1 mg/L. The overproduction of ROS led to a decrease of antioxidant and nitrogen removal enzyme activities, and upregulation of the porin gene increased the risk of GD entering the intracellular space upon exposure to GD at concentrations higher than 1 mg/L. Some denitrifiers survived via resistance and their basic capabilities of sugar metabolism and nitrogen assimilation. Notably, low concentrations of disinfectants could promote vertical and horizontal transfer of multiple resistance genes, especially aminoglycosides, among microorganisms, which might increase not only the adaptation capability of denitrifiers but also the risk to ecological systems. Therefore, the risks of disinfectants targeting ASF on ecology and health as well as the effects of disinfectant residuals from the COVID-19 epidemic should receive more attention.